Mobile Learning in EFL Classroom: Barriers and Prospects in Sikka - Muhammad Zakki Yamani; Rikardus Nasa; Velmi Mayaputri (Yayasan Pendidikan Bima Berilmu, 2025)
The integration of internet-based learning systems, particularly mobile learning (M-learning), in English education has shown promising potential in enhancing students' academic performance and engagement. However, its optimal implementation remains a challenge, especially in the Sikka regency of East Nusa Tenggara province. This study aims to uncover the challenges and opportunities associated with M-learning encountered by participants in Sikka regency. The research employed a quantitative method. Data collection was carried out through the distribution of questionnaires. The obtained data was subsequently analyzed using descriptive analysis techniques. The result of this study identifies several key barriers, including inadequate internet access in remote areas, limited technological proficiency among educators, and concerns regarding students' exposure to inappropriate online content, cyberbullying, and digital exploitation. Furthermore, the insufficient ability of teachers to effectively integrate m-learning into their teaching practices hinders the optimal utilization of m-learning's potential. Therefore, to fully leverage the advantages of m-learning within the educational environment, it is crucial for stakeholders, particularly government agencies and educational organizations, to address the identified challenges.